2012
DOI: 10.1089/dia.2011.0158
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Hypoglycemia Identified by a Continuous Glucose Monitoring System in Patients with Primary Adrenal Insufficiency (Addison's Disease)

Abstract: Background: Hypoglycemia can be a symptom in patients with Addison's disease. The common regimen of replacement therapy with oral glucocorticoids results in unphysiological low cortisol levels in the early morning, the time of highest insulin sensitivity. Therefore patients with Addison's disease are at risk for unrecognized and potentially severe nocturnal hypoglycemia also because of a disturbed counterregulatory function. Use of a continuous glucose monitoring system (CGMS) could help to adjust hydrocortiso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 14 publications
1
27
0
1
Order By: Relevance
“…Previous research has demonstrated that morning glucose levels are lower in adult AI patients [39, 74, 75], and that occult nocturnal hypoglycaemia can occur among adults with AI [76, 77]. As we have described previously [15], the underlying mechanism for this is likely to involve reduced nocturnal gluconeogenesis during an overnight fast, a process that is partially dependent on glucocorticoids.…”
Section: Future Research Directionssupporting
confidence: 52%
“…Previous research has demonstrated that morning glucose levels are lower in adult AI patients [39, 74, 75], and that occult nocturnal hypoglycaemia can occur among adults with AI [76, 77]. As we have described previously [15], the underlying mechanism for this is likely to involve reduced nocturnal gluconeogenesis during an overnight fast, a process that is partially dependent on glucocorticoids.…”
Section: Future Research Directionssupporting
confidence: 52%
“…One patient was detected to have nocturnal hypoglycemia with a blood glucose concentration of less than 50 mg/dL. When the patient's last hydrocortisone dosing was changed to late evening, there were no further episodes of hypoglycemia (112).…”
Section: Hypoglycemia In Adrenal Insufficiencymentioning
confidence: 99%
“…The study by Christiansen et al demonstrated that acute withdrawal of cortisol increased insulin sensitivity close to 70%, increased glucose oxidation by 50%, with decreased endogenous glucose production, implying that adrenocortical failure could result in hypoglycemia (111). Meyer et al studied 13 patients with primary adrenal insufficiency using continuous glucose monitoring for 3-5 days (112). One patient was detected to have nocturnal hypoglycemia with a blood glucose concentration of less than 50 mg/dL.…”
Section: Hypoglycemia In Adrenal Insufficiencymentioning
confidence: 99%
“…Studies in secondary adrenal insufficiency indicate that altered circadian cortisol patterns during replacement therapy affect both carbohydrate and lipid metabolism (82,83), but the effects of glucocorticoid and growth hormone failure and their replacement are hard to distinguish. It is, however, likely that lack of night-time cortisol in patients on regular glucocorticoid replacement therapy confers risk of nocturnal hypoglycaemia, which may be a problem particular to patients with concomitant diabetes mellitus (84). Use of once-daily modified release hydrocortisone tablet (Plenadren, Viropharma Inc, Exton, PA, USA) resulted in decreased body mass index (BMI) and HbA1c compared with conventional hydrocortisone treatment (43,85).…”
Section: Metabolismmentioning
confidence: 99%